Propuesta de un plan de eficiencia energética en el hotel Chrisban Hotel Boutique (2021)
The present study focused on carrying out a characterization of energy consumption in the Chrisban Hotel Boutique in order to propose alternatives for the adoption of strategies focused on obtaining greater energy efficiency, determining criteria and requirements applicable to the hotel based on the ISO 50001 standard. Therefore, an energy management system was designed under the continuous improvement cycle PHVA (PlanDo-Verify-Act) together with three proposals for the reduction of electricity consumption, mainly in the changes of technologies to LED lighting, the use of inverter technology in air conditioning equipment, in addition to an alternative in the use of photovoltaic solar energy.